Multiple Endocrine Neoplasia Type 1: A case report (Research, Society and Development, 2021)
Objective: To discuss about a rare case of type 1 multiple endocrine neoplasia and discuss issues related to the importance of early diagnosis. Methods: Information provided through medical record review, interview with the patient, photographic record of the exams to which the patient was submitted. Case report: Female, 60 years old, previous history of secondary amenorrhea since she was 18 years old. At the time, stylist gynecologist, in which hyperprolactinemia was verified and bromocriptine was prescribed. She remained without endocrinological follow-up for approximately forty years, when she was referred for specialized consultation. In consultation, hyperprolactinemia, hypercalcemia and elevated PTH were observed. In addition to imaging exams with pituitary microadenoma, thyroid, pancreatic and adrenal nodules. With the clinical diagnosis of NEM1, the patient and some family members are currently being called upon to collect genetic material for analysis and detection of the mutation profile. Conclusion: It was possible to conclude that Multiple Endocrine Neoplasia Type 1, if not diagnosed at the beginning, can cause important hormonal syndromes, just as it is important to be considered among the differential diagnoses.